Research on professional responsibility and ethics in accounting. Vol. 19 - Jeffrey, Cynthia (Bingley, U.K. : Emerald, 2015)
Research on Professional Responsibility and Ethics in Accounting publishes high-quality research and cases which focus on the professional responsibilities of accountants and how they deal with the ethical issues they face. Covering timely issues such as social responsibility and ethical judgement, the series brings together a range of articles exploring the professional responsibilities of accountants, codes of conduct which affect them, and securities regulations. Compliance with professional guidelines is judgement-based and the characteristics of the individual, the culture in which they operate, and situations all affect how these guidelines are interpreted and applied, as well as when they might be violated.
Standalone corporate social responsibility reports and stock market returns / William LaGore, Lois Mahoney, Linda Thorne -- How does moral intensity impact the moral judgments and whistleblowing intentions of professional accountants? / Tara J. Shawver, Lynn H. Clements, John T. Sennetti -- The importance of ethics and ethical leadership in the accounting profession / Mary Kay Copeland -- Whistleblowing considerations for external auditors under Dodd-Frank : a blueprint for future research / Steven Mintz -- Benefit corporations as a socially responsible business model : the role of accounting / Charles J. Coate, Mark C. Mitschow -- The effectiveness of instruction in accounting ethics education : another look / David J. Burns, James A. Tackett, Fran Wolf -- Religious social identity and whistle-blowing / Daniel Ames, Deborah L. Seifert, Jay Rich.
Print version record
Keywords: Business & Economics -- Accounting -- General; Accounting; Accountants -- Professional ethics; Accounting -- Moral and ethical aspects